Supporting dementia caregivers: The role of “lived experience” and public health collaboration - Chelsea Kline; Elma Johnson; Ellen Tambor; Catherine Woodall Colcombe; Sam Fazio; Greg Woods; Dale Rivard; Gary Epstein‐Lubow (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2025)
Abstract Developing effective resources to support dementia caregivers requires collaboration between public health officials and those with lived experience of caregiving. This perspective highlights why this collaboration is so crucial to elevating public health practice and describes the unique efforts of the BOLD Public Health Center of Excellence on Dementia Caregiving to foster this collaboration through its Lived Experience Advisory Groups (LEAG). The LEAGs convene people living with dementia, family caregivers, and public health officials to guide the development of resources that state, local, and tribal public health departments can use to support dementia caregivers in their communities. Through these interactions, public health strategies become more responsive to the real‐life needs of caregivers and people living with dementia. This approach not only enhances caregiver support but also strengthens and aligns public health initiatives with the lived experiences of the populations they serve, fostering health equity and community engagement. This paper highlights key activities, outcomes, and future directions for integrating lived experience and public health perspectives into practice, offering a new and innovative model for other organizations seeking to improve support for dementia caregivers. Highlights Public engagement enhances responsiveness and effectiveness of public health programs. LEAGs allow people with lived experience to help shape programs and facilitate collaboration with public health professionals. Local and state health agencies can improve engagement by implementing LEAGs. Increasing diversity of people with lived experience can improve outcomes for communities disproportionately impacted by dementia.